Analysis of the participation of Bosnia and Herzegovina and Croatia in the UNESCO's Memory of the World Programme - Kodrić Zaimović, Lejla (2012)
The authors analyse the level of participation of Bosnia and Herzegovina and Croatia, countries of the so called Western Balkans, in the respectable UNESCO's Memory of the World Programme. The initial presumption is that they participate in different ways and with different intensity. Processes of nomination and registration of documentary heritage of those countries for the Memory of the World Programme depend not only on the specific social circumstances but also on the activities within local heritage communities. The authors present the level of participation of archival, library and museum materials of the two countries' heritage institutions in the Memory of the World Register. The paper provides an insight in the current activities in Bosnia and Herzegovina and Croatia, based on the results of the web-based survey conducted in the two neighbouring countries checking the awareness of and participation in the UNESCO's Programme. All of the most important archival, library and museum institutions in both countries were surveyed. The results are analysed and compared on the level of each country, between the two countries, and finally in the international context, using the results of an earlier Survey on global familiarity with the Memory of the World Programme during which Bosnia and Herzegovina and Croatia were not surveyed. The authors question the reasons for (non)participation in the Programme and suggest further actions that are necessary for preservation and presentation of the documentary heritage of Bosnia and Herzegovina and Croatia, which include items important for the world heritage.